Q: What is 3 x4 x 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

sqrt(x4) = x4/2 = x2

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

2 cubes wide x 3 cubes long x 4 cubes high. 2 X 3 X4 6 X 4 24 cubes

x4 + 3x3 - x2 - 9x - 6 = 0 x4 + x3 + 2x3 + 2x2 - 3x2 - 3x - 6x - 6 = 0 x3(x + 1) + 2x2(x + 1) - 3x(x + 1) - 6(x + 1) = 0 (x + 1)(x3 + 2x2 - 3x - 6) = 0 (x + 1)[x2(x + 2) - 3(x + 2)] = 0 (x + 1)(x + 2)(x2 - 3) = 0 So x + 1 = 0 so that x = -1 or x + 2 = 0 so that x = -2 or x2 - 3 = 0 so that x = +/- sqrt(3)

x4 - x2 - 12 = (x2 + 3) (x2 - 4)And (x2 - 4) = (x + 2) (x - 2)So the original expression = (x2+ 3) (x + 2) (x - 2)

Related questions

(x^2 - 3)(x^2 + 3)

(x - 2)(x + 2)(x - 3)(x + 3)

I assume the x4 is x to the 4th power, and x2 is x², or x squared. The two factors would be: (x + 2)(x - 2)(x² + 3) There are 4 solutions for x: x = 2 x = -2 x = √-3 x = -√-3

(x4 - 3)(x4 + 3)

Greatest common factor of x4 and x3 is x3.

(x - 3)(x + 1)(x + 2)(x + 4)

3x3 + 6x2 + x + 2 3x2 (x + 2) + (x + 2) (x + 2) (3x2 + 1) OR 3x3 + x + 6x2 + 2x (3x2 + 1) + 2 (3x2 + 1) (3x2 + 1) (x + 2) Check: (x + 2) (3x2 + 1) = 3x3 + x + 6x2 + 2 = 3x3 + 6x2 + x + 2 x3 - 3x2 - 4x + 12 x2 (x - 3) - 4 (x - 3) (x - 3) (x2 - 4) (x - 3) (x + 2) (x - 2) Check: (x - 3) (x + 2) (x - 2) = (x - 3) (x2 - 4) = x3 - 4x - 3x2 + 12= x3 - 3x2 - 4x + 12=== === x5 - x4 + 8x3 - 8x2 + 16x - 16 x4 (x - 1) + 8x2 (x - 1) + 16 (x - 1) (x - 1) (x4 + 8x2 + 16) (x - 1) (x2 + 4)(x2 + 4) (x - 1) (x2 + 4)2 Real Solution (x - 1) (x + 2i) (x - 2i) (x + 2i) (x - 2i) (x - 1) (x + 2i)2 (x - 2i)2 Check: (x - 1) (x + 2i)2 (x - 2i)2 = (x - 1) (x + 2i) (x - 2i) (x + 2i) (x - 2i) = (x - 1) (x2 + 2xi - 2xi - 4i2) (x2 + 2xi - 2xi - 4i2) = (x - 1) (x2 - 4(-1)) (x2 - 4(-1)) = (x - 1) (x2 + 4) (x2 + 4) = (x - 1) (x4 + 4x2 + 4x2 +16) = (x - 1) (x4 + 8x2 + 16) = x5 + 8x3 +16x - x4 - 8x2 - 16 = x5 - x4 + 8x3 - 8x2 + 16x - 16

264

(x - 2)(x + 2)(x^2 + 4)

x4 - 4x3 - 12x2 -32x + 64 (x - 4)(x + 2)(x + 2)(x - 4)

This is written x4/3 . In fractional exponents, the denominator is the root and the numerator is the power. It may help to note that x 1/3 is another way to write "cube root of x" and x4/3 = (x4)1/3

x4+100=29x2 x4+100-29x2=0 (X2)2+100-29x2=0 (x2-25)(x2-4)=0 (x+5)(x-5)(x+2)(x-2) x=-5 x=5 x=-2 x=2